Personalized data-driven prediction algorithms for glycemic trend : doctoral thesis - Žulj, Sara; Magjarević, Ratko; Carvalho, Paulo de (Professor of informatics engineering) (Zagreb : S. Žulj ; Faculty of electrical engineering and computing, 2022)
An important aspect of diabetes management is controlling the glucose level. A step towards achieving the control is monitoring and taking actions (e.g., administering insulin) to avoid dangerous levels. Predicting future values may allow the user to be alerted when an action is needed. This thesis investigates an interpretable case-based reasoning (CBR) model for predicting future glucose levels. The focus of this work lies in exploring the different hyperparameters of CBR model. The work also ev104 - 117aluates the effect of meal intake as an input variable in a data-driven way. This is in contrast to previously published research which use dedicated physiological models to include the meal. The effect of the dataset size on the prediction error is modelled. Models are often trained on very small datasets and reported error often does not reflect the large variance caused by the dataset size. Further, the personalization of the CBR model by clustering the patient data prior to building the CBR model’s case base is studied. The clustering is done using clinical, behavioral, anthropometric and demographic data. Finally, a new two-stage method for maintaining the case base of the CBR regression problem is proposed.
The contributions are:
• A case-based reasoning model for prediction of glucose levels,
• A personalization of the model through a clustering strategy,
• A method for updating and maintaining the case base.
Kontrola razine glukoze važan je aspekt upravljanja dijabetesom. Korak prema ostvarivanju kontrole je praćenje i poduzimanje adekvatnih radnji (npr. davanje inzulina) kako bi se izbjegle opasne razine. Predviđanje budućih vrijednosti omogućuje upozorenja korisniku kako bi na vrijeme poduzeo potrebne radnje. Ovaj rad istražuje interpretabilan model temeljen na zaključivanju na temelju slučaja (CBR) za predviđanje budućih razina glukoze. Fokus istraživanja leži u odabiru različitih hiperparametara CBR modela. Također, istražen je učinak unosa obroka kao ulazne varijable na podatkovno-vođeni način. To je u suprotnosti s prethodno objavljenim istraživanjima koja koriste fiziološke modele kako bi uključili obrok. Modeliran je učinak veličine skupa podataka na pogrešku predviđanja. Modeli često uče na vrlo malim skupovima podataka te iskazana pogreška modela često ne odražava značajnu varijancu pogreške uzrokovanu veličinom skupa podataka. Nadalje, istražena je personalizacija CBR modela grupiranjem podataka o pacijentu prije izgradnje baze slučajeva CBR modela. Grupiranje se provodi pomoću kliničkih podataka, podataka o ponašanju, antropometrijskih i demografskih podataka. Konačno, predložena je nova metoda u dvije faze za održavanje baze slučajeva CBR regresijskog problema.
Ostvareni doprinosi su:
• Model temeljen na zaključivanju na temelju slučaja za predviđanje razine glukoze,
• Personalizacija modela kroz strategiju grupiranja,
• Metoda za ažuriranje i održavanje baze slučajeva.
Bibliografija : str. 104 - 117